Totally laparoscopic total gastrectomy with technique of functional end-to-end esophagojejunostomy by linear stapler without previous resection of the esophagus and jejunum - Chien, Dinh Van; Huong, Nguyen Van; Khoa, Dang Dinh; Thuy, Nguyen Van; Quyet, Ha Van; Duyet, Pham Van; Thuong, Pham Van; Ai, Dang Quaoc (International Surgery Journal, 2020)
Background: The technique of esophagojejunostomy in totally laparoscopic total gastrectomy is difficult and had a high frequency of incidents during surgery and anastomotic leakage. We aimed to evaluate the outcomes of the technique of functional end-to-end esophagojejunostomy by linear stapler without previous resection of the esophagus and jejunum in the totally laparoscopic total gastrectomy with D2 lymph node dissection in the treatment of gastric cancer. Methods: A prospective observational study on patients received technique of functional end-to-end esophagojejunostomy by linear stapler without previous resection of esophagus and jejunum between July 2017 to July 2020. Results: We included 70 patients with a mean age of 62.5. There were 80% of patients having tubular adenocarcinoma and papillary adenocarcinoma, 11.4% of patients having tumors in the upper third of the stomach, and 81.4% of patients having tumors in the middle of the stomach. There were 4.2% of cases having incidents during the surgery and 2.8% of cases having complications after the surgery. No anastomotic leakage or death was observed after the surgery. The mean lymph node was 23, and the mean metastatic lymph node was 2.7. The operation time was 203.8 minutes. The mean hospital stay was 8.0 days. The one year survival after the surgery was 97.9%, and two year survival was 93.1%. The mean survival was 35.3 months. Conclusions: TLTG with D2 lymph node dissection using functional end-to-end esophagojejunostomy by linear stapler without previous resection of esophagus and jejunum was safe and effective in gastric cancer treatment.